Ruthenium / nano cerium dioxide-based heterojunction catalyst as well as preparation method and application thereof

The nano-ceria heterojunction support was prepared by co-precipitation method and mixed with the ruthenium source. The ruthenium/nano-ceria-based heterojunction catalyst was formed by ultraviolet light reduction treatment, which solved the problems of high reaction temperature, large energy consumption and high precious metal content of the existing ammonia decomposition hydrogen production catalyst, and achieved efficient ammonia decomposition hydrogen production at lower temperatures, reducing energy consumption and improving the stability of the catalyst.

CN119733508AActive Publication Date: 2025-04-01ZHEJIANG UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510009722.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-01
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

The existing ammonia decomposition hydrogen production catalysts have problems such as high reaction temperature, large energy consumption, high content of noble metal ruthenium and high cost, and are prone to sintering and inactivation, and lack regeneration properties.

Method used

The co-precipitation method is used to prepare nano-ceria heterojunction support and mix it with the ruthenium source. Through ultraviolet light reduction treatment, a ruthenium/nano-ceria-based heterojunction catalyst is formed to ensure uniform distribution of the ruthenium precursor and uniform dispersion of metal ruthenium, and avoid structural damage caused by particle aggregation and high-temperature calcination.

Benefits of technology

It realizes efficient ammonia decomposition and hydrogen production at lower temperatures (500°C), which reduces energy consumption, improves the activity and selectivity of the catalyst, extends the stability and life of the catalyst, and reduces the production of chemical waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733508A_ABST
    Figure CN119733508A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, in particular to a ruthenium / nano cerium dioxide based heterojunction catalyst and a preparation method and application thereof, and is characterized in that the preparation method comprises the following steps: (1) precipitating cerium salt on a metal oxide substrate through a coprecipitation method, and performing aging and roasting treatment to obtain a nano cerium dioxide heterojunction carrier; and (2) mixing the nano cerium dioxide heterojunction carrier with a ruthenium source, and carrying out ultraviolet light reduction treatment to obtain the ruthenium / nano cerium dioxide-based heterojunction catalyst. The ruthenium / nano cerium dioxide-based heterojunction catalyst prepared by the invention can catalyze ammonia gas decomposition at 500 DEG C to prepare hydrogen, and the ammonia gas conversion rate can reach 99.7%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a ruthenium / nano-cerium dioxide-based heterojunction catalyst, a preparation method and application thereof. Background Art

[0002] Hydrogen energy is an important technical approach to achieving the dual carbon goals, but the storage and transportation of hydrogen has always been a bottleneck restricting the development of the hydrogen energy industry. Ammonia-to-hydrogen energy can not only solve the problem of hydrogen storage and transportation, and improve the stability and security of energy supply, but also achieve carbon-free emissions of terminal energy, which is of great significance for promoting the transformation of our energy structure to green and low-carbon.

[0003] The main catalysts for hydrogen production from ammonia decomposition are Ru-based, Ni-based and Fe-based. Ni-based and Fe-based catalysts generally face the problems of high reaction temperature and high energy consumption. Due to its excellent activity, Ru-based catalysts can reduce the reaction temperature of ammonia decomposition to 500°C, but Ru as a precious metal has a high cost, and the Ru metal content in high-activity catalysts must reach more than 2wt%, resulting in high costs. In addition, Ru-based catalysts are easily sintered and deactivated, and do not have regeneration performance. The catalyst can only be remade by recovering Ru precious metal. Therefore, it is particularly important to design highly stable and highly active precious metal-support catalysts. In the prior art, patent CN 118403640 A provides a method for preparing a ruthenium-based catalyst, which comprises mixing a ruthenium source with a carrier and calcining to obtain a precursor; mixing the precursor (or the reduced precursor) with a sulfur source, and modifying the precursor by calcination or atomic layer deposition multiple pulse strategy to obtain the ruthenium-based catalyst. The prepared ruthenium-based catalyst has high CO 2 Catalytic hydrogenation activity.

[0004] However, the method provided by the above method requires mixing the precursor with a sulfur source and performing a modification treatment, which may introduce additional impurities and potential pollution problems. At the same time, the method involves multiple calcination steps involving ruthenium active components and the calcination temperature is as high as 800°C, which may lead to sintering of the ruthenium active component. Summary of the invention

[0005] The present invention is made to solve the above-mentioned problems, and aims to provide a ruthenium / nano-cerium dioxide-based heterojunction catalyst, a preparation method and application thereof.

[0006] The first aspect of the present invention provides a method for preparing a ruthenium / nano-ceria-based heterojunction catalyst, characterized in that it comprises the following steps: (1) precipitating cerium salt on a metal oxide substrate by a co-precipitation method, and subjecting the substrate to aging and calcination to obtain a nano-cerium dioxide heterojunction carrier; (2) The nano-cerium dioxide heterojunction carrier is mixed with a ruthenium source, and after ultraviolet light reduction treatment, the ruthenium / nano-cerium dioxide-based heterojunction catalyst is obtained.

[0007] The present invention uses a coprecipitation method to uniformly precipitate cerium salt on a metal oxide substrate, which helps to form highly dispersed nano-cerium dioxide particles, and nano-sized cerium dioxide has a large specific surface area, which can provide more active sites for the subsequent attachment of ruthenium. At the same time, the maturation and crystallization of nano-cerium dioxide are promoted by aging to improve its stability, and calcination is used to remove moisture and organic matter in the nano-cerium dioxide particles to form a stable nano-cerium dioxide structure.

[0008] Furthermore, since cerium dioxide has Ce 3+ / Ce 4+ The variable valence property of ceria enables it to store oxygen and donate electrons, which enables it to transfer electrons to Ru metal, thereby reducing the breaking energy barrier of the NH bond and promoting the decomposition reaction of ammonia. However, ceria has poor stability and may undergo phase change or structural collapse at high temperatures. It is not stable enough in acidic environments, which will affect the stability and life of the catalyst and its application under certain acidic reaction conditions. On the other hand, using ceria alone may make it difficult to achieve a uniform distribution of active sites, thus affecting the efficiency and selectivity of the catalyst.

[0009] Therefore, the present invention uses a combination of metal oxides and ceria to overcome the limitations of a single ceria carrier and improve the overall performance of the catalyst. The heterojunction formed between the metal oxide substrate and nano ceria can promote electron transfer and enhance catalyst performance. The introduction of metal oxides can promote the uniform distribution of active sites, improve the activity and selectivity of the catalyst, and by combining with different metal oxides, the different properties of the catalyst can be improved. For example, by combining with metal oxides with better thermal stability, the thermal stability of the overall catalyst can be improved; by combining with alumina, since alumina has good stability in an acidic environment, ceria can be protected from erosion by acidic conditions; by combining with titanium oxide, the mechanical strength of the overall structure of the catalyst can be enhanced.

[0010] Furthermore, the present invention mixes a ruthenium source with a nano-cerium dioxide heterojunction carrier to ensure that the ruthenium precursor is evenly distributed on the carrier surface, uses ultraviolet light irradiation reduction treatment to stimulate the reduction reaction of the ruthenium precursor, converts it into metallic ruthenium with catalytic activity, and makes the metallic ruthenium evenly dispersed on the nano-cerium dioxide heterojunction carrier, avoiding the problem of particle aggregation that may be caused by simple mixing and calcination, and can form more uniform and smaller metallic ruthenium nanoparticles, which can increase the number and diversity of active sites of the catalyst, thereby improving the catalytic efficiency.

[0011] At the same time, UV irradiation can be carried out at a lower temperature, which is milder than high-temperature calcination. It avoids the damage to the carrier structure that may be caused by high-temperature calcination, helps to maintain the stability of the catalyst structure, reduces thermal damage, and does not require the use of additional chemical reagents, such as sulfur sources, which reduces the generation of chemical waste and is more environmentally friendly.

[0012] The present invention can increase the coupling of metal ruthenium and ceria by ultraviolet light irradiation, so that highly dispersed metal ruthenium is loaded on the ceria carrier in a directional manner and deposited on the metal oxide substrate, and the interaction between Ru and ceria is enhanced, and the agglomeration of metal ruthenium is effectively suppressed. This structural design not only enhances the interaction between metal ruthenium and ceria, but also promotes the electron transfer process from the metal oxide substrate to ceria and then to metal ruthenium. This electron transfer mechanism significantly reduces the dissociation barrier of the NH bond in the ammonia decomposition reaction, thereby accelerating the reaction rate and improving the reaction activity of the catalyst.

[0013] The present invention achieves efficient ammonia decomposition to produce hydrogen at a relatively low temperature (500°C) by optimizing the interaction between metallic ruthenium and nano-cerium dioxide, which is of great significance for reducing energy consumption and improving catalytic efficiency.

[0014] In some embodiments, in step (1), the ruthenium source is ruthenium chloride or carbonyl ruthenium, and the content of ruthenium element in the ruthenium source is 0.5wt%-3wt% of the nano-cerium dioxide heterojunction carrier.

[0015] In some embodiments, in step (1), the cerium salt is precipitated on the metal oxide substrate using one of ammonia water, sodium carbonate or potassium hydroxide as a precipitant.

[0016] In some embodiments, in step (1), the metal oxide substrate is one of aluminum oxide, titanium oxide, magnesium oxide, zinc oxide or molybdenum oxide.

[0017] In some embodiments, in step (1), the cerium salt is one of cerium nitrate, ammonium cerium nitrate, cerium chloride or cerium sulfate.

[0018] In some embodiments, in step (1), in the nano-cerium dioxide heterojunction carrier, the particle size of the nano-cerium dioxide is 5-20 nm.

[0019] In the embodiment, the cerium salt is uniformly precipitated on the metal oxide substrate by coprecipitation, which helps to form highly dispersed nano-cerium dioxide particles. The formed nano-cerium dioxide is 5-20nm, which has a higher specific surface area, which means that more active sites can be used for catalytic reactions, thereby improving catalytic efficiency. When nano-cerium dioxide forms a heterojunction with other metal oxides, a synergistic effect can be generated, which helps to improve the overall performance of the catalyst.

[0020] In some embodiments, in step (1), the precipitation pH is 8-12, the aging time is 4-24 hours, and the calcination temperature is 500-800°C.

[0021] In some embodiments, the step (2) specifically comprises: mixing the nano-cerium dioxide heterojunction carrier with a ruthenium source, irradiating the mixture with a 200-400W UV lamp for 0.5-4 hours, centrifuging, washing and drying at 100-120°C to obtain the ruthenium / nano-cerium dioxide-based heterojunction catalyst.

[0022] The second aspect of the present invention provides a ruthenium / nano-ceria-based heterojunction catalyst, characterized in that the ruthenium / nano-ceria-based heterojunction catalyst is prepared by the preparation method described in the first aspect.

[0023] The third aspect of the present invention provides an application of a ruthenium / nano-ceria-based heterojunction catalyst, characterized in that the reaction temperature is 400-700°C, the reaction pressure is 0-1MPa, and the space velocity is 1000-50000h -1 Under the conditions of, the ruthenium / nano-ceria-based heterojunction catalyst prepared by the preparation method described in the first aspect or the ruthenium / nano-ceria-based heterojunction catalyst described in the second aspect is used to catalyze the decomposition of ammonia to produce hydrogen.

[0024] By implementing the above technical solution, the present invention has the following beneficial effects: The present invention uses a coprecipitation method to uniformly precipitate cerium salt on a metal oxide substrate, which helps to form highly dispersed nano-cerium dioxide particles, and nano-sized cerium dioxide has a large specific surface area, which can provide more active sites for the subsequent attachment of ruthenium. The present invention uses a combination of metal oxide and cerium dioxide to overcome the limitations of a single cerium dioxide carrier and improve the overall performance of the catalyst. The heterojunction formed between the metal oxide substrate and the nano-cerium dioxide can promote electron transfer and enhance the catalyst performance.

[0025] The present invention mixes a ruthenium source with a nano-cerium dioxide heterojunction carrier to ensure that the ruthenium precursor is evenly distributed on the carrier surface, uses ultraviolet light irradiation reduction treatment to stimulate the reduction reaction of the ruthenium precursor, converts it into metallic ruthenium with catalytic activity, and makes the metallic ruthenium evenly dispersed on the nano-cerium dioxide heterojunction carrier, avoiding the problem of particle aggregation that may be caused by simple mixing and calcination, forming more uniform and smaller metallic ruthenium nanoparticles, increasing the number and diversity of active sites of the catalyst, and thus improving the catalytic efficiency.

[0026] At the same time, UV irradiation can be carried out at a lower temperature, which is milder than high-temperature calcination. It avoids the damage to the carrier structure that may be caused by high-temperature calcination, helps to maintain the stability of the catalyst structure, reduces thermal damage, and does not require the use of additional chemical reagents, such as sulfur sources, which reduces the generation of chemical waste and is more environmentally friendly.

[0027] The present invention loads metal ruthenium onto nano-cerium dioxide in a directional manner through the above method, and ruthenium / nano-cerium dioxide is deposited on a metal oxide substrate, which inhibits the agglomeration of metal ruthenium in the catalytic reaction. At the same time, the metal oxide substrate can transmit electrons to the cerium dioxide, and the cerium dioxide further transmits electrons to the metal ruthenium, which promotes the dissociation of the NH bond in the ammonia decomposition reaction, accelerates the reaction rate, and improves the reaction activity. The ruthenium / nano-cerium dioxide-based heterojunction catalyst prepared by the present invention can catalyze the decomposition of ammonia to produce hydrogen at 500°C, and the ammonia conversion rate can reach 99.7%. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 XRD characterization of the catalysts prepared in Example 1, Comparative Example 8 and Comparative Example 9 of the present invention; Figure 2 TEM characterization of the catalyst prepared in Example 1 of the present invention; Figure 3 TEM characterization of the catalyst prepared in Comparative Example 9 of the present invention; Figure 4 Ammonia decomposition and hydrogen production reaction performance diagram of the catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] In order to make the technical means, creative features, objectives and effects achieved by the present invention easier to understand, the present invention is described in detail below in conjunction with embodiments and drawings.

[0030] Example 1 10.0 g of titanium oxide was dispersed in a beaker containing 100 mL of water and stirred at 300 r / min with a stirring paddle to form a suspension. 50 mL of cerium nitrate hexahydrate solution (containing 16.2 g of cerium nitrate hexahydrate) and 6 M ammonia water were co-dropped into the beaker, and the pH was controlled to be constant at 9.5. After the addition was completed, the mixture was aged for 24 h, then washed and dried in an oven at 120 ° C for 8 h, and then calcined in a muffle furnace at 500 ° C for 6 h to obtain CeO 2 -TiO 2 Heterojunction support, CeO 2 The average particle size is about 5.7nm.

[0031] 5 g CeO 2 -TiO 2The heterojunction carrier was dispersed in a beaker containing 100 mL of water and stirred at 800 r / min with a magnetic stirrer to form a suspension. A solution containing 0.102 g of ruthenium chloride was added, wherein the mass of the ruthenium element was CeO 2 -TiO 2 1wt% of the heterojunction carrier was irradiated with 300W ultraviolet light for 1h, centrifuged, washed and dried in an oven at 120℃ to obtain 1wt%Ru / nano-CeO 2 -TiO 2 Heterojunction catalyst.

[0032] Example 2 10.0 g of titanium oxide was dispersed in a beaker containing 100 mL of water and stirred at 300 r / min with a stirring paddle to form a suspension. 50 mL of cerium nitrate hexahydrate solution (containing 16.2 g of cerium nitrate hexahydrate) and 6 M ammonia water were co-dropped into the beaker, and the pH was controlled to be constant at 9.5. After the addition was completed, the mixture was aged for 24 h, then washed and dried in an oven at 120 ° C for 8 h, and then calcined in a muffle furnace at 500 ° C for 6 h to obtain CeO 2 -TiO 2 Heterojunction support, CeO 2 The average particle size is about 5.7nm.

[0033] 5 g CeO 2 -TiO 2 The heterojunction carrier was dispersed in a beaker containing 100 mL of water and stirred at 800 r / min with a magnetic stirrer to form a suspension. A solution containing 0.051 g of ruthenium chloride was added, wherein the mass of the ruthenium element was CeO 2 -TiO 2 0.5wt% of the heterojunction carrier was irradiated with 300W ultraviolet light for 1h, centrifuged, washed and dried in an oven at 120℃ to obtain 0.5wt%Ru / nano-CeO 2 -TiO 2 Heterojunction catalyst.

[0034] Example 3 10.0 g of titanium oxide was dispersed in a beaker containing 100 mL of water and stirred at 300 r / min with a stirring paddle to form a suspension. 50 mL of cerium nitrate hexahydrate solution (containing 16.2 g of cerium nitrate hexahydrate) and 6 M ammonia water were co-dropped into the beaker, and the pH was controlled to be constant at 9.5. After the addition was completed, the mixture was aged for 24 h, then washed and dried in an oven at 120 ° C for 8 h, and then calcined in a muffle furnace at 600 ° C for 6 h to obtain CeO 2 -TiO 2 Heterojunction support, CeO 2 The average particle size is about 5.7nm.

[0035] 5 g CeO 2 -TiO 2 The heterojunction carrier was dispersed in a beaker containing 100 mL of water and stirred at 800 r / min with a magnetic stirrer to form a suspension. A solution containing 0.153 g of ruthenium chloride was added, wherein the mass of the ruthenium element was CeO 2 -TiO 2 1.5wt% of the heterojunction carrier was irradiated with 300W ultraviolet light for 1h, centrifuged, washed and dried in an oven at 120℃ to obtain 1.5wt%Ru / nano-CeO 2 -TiO 2 Heterojunction catalyst.

[0036] Example 4 10.0 g of titanium oxide was dispersed in a beaker containing 100 mL of water and stirred at 300 r / min with a stirring paddle to form a suspension. 50 mL of cerium nitrate hexahydrate solution (containing 16.2 g of cerium nitrate hexahydrate) and 6 M potassium hydroxide were co-dropped into the beaker, and the pH was controlled to be constant at 9. After the addition was completed, the mixture was aged for 24 h, then washed and dried in an oven at 120 ° C for 8 h, and then calcined in a muffle furnace at 600 ° C for 6 h to obtain CeO 2 -TiO 2 Heterojunction support, CeO 2 The average particle size is about 8.1 nm.

[0037] 5 g CeO 2 -TiO 2 The heterojunction carrier was dispersed in a beaker containing 100 mL of water and stirred at 800 r / min with a magnetic stirrer to form a suspension. A solution containing 0.105 g of carbonyl ruthenium was added, wherein the mass of the ruthenium element was CeO 2 -TiO 2 1wt% of the heterojunction carrier was irradiated with 300W ultraviolet light for 1h, centrifuged, washed and dried in an oven at 120℃ to obtain 1wt%Ru / nano-CeO 2 -TiO 2 Heterojunction catalyst.

[0038] Example 5 10.0 g of cerium oxide was dispersed in a beaker containing 100 mL of water and stirred at 300 r / min with a stirring paddle to form a suspension. 50 mL of cerium nitrate hexahydrate solution (containing 16.2 g of cerium nitrate hexahydrate) and 6 M potassium hydroxide were co-dropped into the beaker, and the pH was controlled to be constant at 9. After the addition was completed, the mixture was aged for 24 h, then washed and dried in an oven at 120 ° C for 8 h, and then calcined in a muffle furnace at 600 ° C for 6 h to obtain CeO 2 -ZrO 2 Heterojunction support, CeO 2The average particle size is about 10.9 nm.

[0039] 5 g CeO 2 -ZrO 2 The heterojunction carrier was dispersed in a beaker containing 100 mL of water and stirred at 800 r / min with a magnetic stirrer to form a suspension. A solution containing 0.105 g of carbonyl ruthenium was added, wherein the mass of the ruthenium element was CeO 2 -TiO 2 1wt% of the heterojunction carrier was irradiated with 300W ultraviolet light for 1h, centrifuged, washed and dried in an oven at 120℃ to obtain 1wt%Ru / nano-CeO 2 -ZrO 2 Heterojunction catalyst.

[0040] Example 6 10.0 g of magnesium oxide was dispersed in a beaker containing 100 mL of water and stirred at 300 r / min with a stirring paddle to form a suspension. 50 mL of cerium nitrate hexahydrate solution (containing 16.2 g of cerium nitrate hexahydrate) and 6 M potassium hydroxide were co-dropped into the beaker, and the pH was controlled to be constant at 9. After the addition was completed, the mixture was aged for 24 h, then washed and dried in an oven at 120 ° C for 8 h, and then calcined in a muffle furnace at 700 ° C for 6 h to obtain CeO 2 -MgO heterojunction support, CeO 2 The average particle size is about 7.3nm.

[0041] 5 g CeO 2 The -MgO heterojunction carrier was dispersed in a beaker containing 100 mL of water and stirred at 800 r / min with a magnetic stirrer to form a suspension. A solution containing 0.105 g of carbonyl ruthenium was added, wherein the mass of the ruthenium element was CeO 2 -TiO 2 1wt% of the heterojunction carrier was irradiated with 300W ultraviolet light for 1h, centrifuged, washed and dried in an oven at 120℃ to obtain 1wt%Ru / nano-CeO 2 -MgO heterojunction catalyst.

[0042] Example 7 10.0 g of titanium oxide was dispersed in a beaker containing 100 mL of water and stirred at 300 r / min with a stirring paddle to form a suspension. 50 mL of cerium nitrate hexahydrate solution (containing 16.2 g of cerium nitrate hexahydrate) and 6 M ammonia water were co-dropped into the beaker, and the pH was controlled to be constant at 9. After the addition was completed, the mixture was aged for 48 h, then washed and dried in an oven at 120 ° C for 8 h, and then calcined in a muffle furnace at 800 ° C for 6 h to obtain CeO 2 -TiO 2 Heterojunction support, CeO 2The average particle size is about 5.7nm.

[0043] 5 g CeO 2 -TiO 2 The heterojunction carrier was dispersed in a beaker containing 100 mL of water and stirred at 800 r / min with a magnetic stirrer to form a suspension. A solution containing 0.105 g of carbonyl ruthenium was added, wherein the mass of the ruthenium element was CeO 2 -TiO 2 1wt% of the heterojunction carrier was irradiated with 300W ultraviolet light for 2h, centrifuged, washed and dried in an oven at 120℃ to obtain 1wt%Ru / nano-CeO 2 -TiO 2 Heterojunction catalyst.

[0044] Comparative Example 8 50 mL of cerium nitrate hexahydrate solution (containing 16.2 g of cerium nitrate hexahydrate) and 6 M ammonia water were co-dropped into a beaker, and the pH was controlled to be constant at 9.5. After the addition was completed, the mixture was aged for 24 h, then washed and dried in an oven at 120 °C for 8 h, and then calcined in a muffle furnace at 500 °C for 6 h to obtain CeO 2 Support, CeO 2 The average particle size is about 59.0nm.

[0045] 5 g CeO 2 The carrier was dispersed in a beaker containing 100 mL of water and stirred at 800 r / min with a magnetic stirrer to form a suspension. A solution containing 0.102 g of ruthenium chloride was added, wherein the mass of the ruthenium element was CeO 2 The carrier was irradiated with 300W UV light for 1h, centrifuged, washed and dried in an oven at 120℃ to obtain 1wt%Ru / CeO 2 catalyst.

[0046] Comparative Example 9 5g TiO 2 The carrier was dispersed in a beaker containing 100 mL of water and stirred at 800 r / min with a magnetic stirrer to form a suspension. A solution containing 0.102 g of ruthenium chloride was added, wherein the mass of the ruthenium element was TiO 2 The carrier was irradiated with 300W UV light for 1h, centrifuged, washed and dried in an oven at 120℃ to obtain 1wt%Ru / CeO 2 catalyst.

[0047] Comparative Example 10 5 g CeO 2 and TiO 2The carriers were mechanically mixed and dispersed in a beaker containing 100 mL of water, stirred at 800 r / min with a magnetic stirrer to form a suspension, and a solution containing 0.102 g of ruthenium chloride was added, wherein the mass of the ruthenium element was CeO 2 and TiO 2 1wt% of the mixed carrier was irradiated under 300W UV light for 1h, centrifuged, washed and dried in an oven at 120℃ to obtain 1wt%Ru / CeO 2 catalyst.

[0048] Comparative Example 11 5 g CeO 2 and TiO 2 The carriers were mechanically mixed and dispersed in a beaker containing 100 mL of water, stirred at 800 r / min with a magnetic stirrer to form a suspension, and a solution containing 0.102 g of ruthenium chloride was added, wherein the mass of the ruthenium element was CeO 2 and TiO 2 The mixed carrier was 1wt%, stirred for 1h, centrifuged, washed, and dried in an oven at 120℃. The powder was calcined at 500℃ in a hydrogen atmosphere for 2h to obtain 1wt%Ru / CeO 2 catalyst.

[0049] Performance Testing The catalysts prepared in Example 1, Comparative Example 8 and Comparative Example 9 were selected for XRD characterization or TEM characterization to obtain Figures 1 to 3 . Figure 1 The XRD characterization of the catalysts of Example 1 and Comparative Examples 8 and 9 is shown. It can be seen that compared with the catalysts prepared in Comparative Examples 8 and 9, the 1 wt% Ru / CeO 2 -TiO 2 The catalyst contains CeO 2 and TiO 2 The characteristic diffraction peak of Ru is highly dispersed and has no obvious peak.

[0050] Figure 2 It shows that the 1wt%Ru / CeO 2 -TiO 2 Transmission electron microscopy image of the catalyst, where TiO 2 It is in the shape of square flakes, nano CeO 2 The Ru clusters are loaded on the nano-CeO 2 superior.

[0051] Figure 3 The 1wt%Ru / TiO 2 Transmission electron microscopy image of the catalyst, where TiO 2It is in the shape of square flakes, and Ru is loaded on TiO 2 The average particle size is about 1.7 nm.

[0052] The performance evaluation parameters of ammonia decomposition hydrogen production reaction are as follows: 2 mL of catalyst was placed in a fixed bed reaction and firstly 2 The catalyst was reduced at 500 °C for 2 h, and then high-purity ammonia was introduced at a space velocity of 20,000 h -1 , the ammonia conversion rate of the catalyst was tested at 500°C. Figure 4 It shows that the catalyst prepared in Example 1 of the present invention has a high thermal conductivity at 500°C and 20000 h. -1 From the graph below showing the change of ammonia conversion rate with reaction time, it can be seen that the catalyst has high stability.

[0053] Table 1 Catalyst performance in the ammonia decomposition to hydrogen reaction (500°C, 20000h -1 ) in the active data record table catalyst Ammonia conversion Example 1 99.7% Example 2 95.1% Example 3 99.7% Example 4 99.6% Example 5 98.8% Example 6 99.2% Example 7 99.7% Comparative Example 8 94.1% Comparative Example 9 90.6% Comparative Example 10 95.5% Comparative Example 11 94.9% In the example, highly dispersed Ru is loaded onto nano-cerium oxide in a directional manner, forming an electron transmission route of oxide substrate-cerium dioxide-Ru, which promotes the decomposition reaction of ammonia. At the same time, the ultraviolet light treatment enhances the interaction between Ru and cerium dioxide, inhibiting the sintering of Ru. In Example 2, the catalytic activity decreases due to the halving of the active component Ru content; in Comparative Example 8, the single-component cerium dioxide carrier has a weak electron supply capacity for Ru; in Comparative Example 9, the TiO 2 The particle size of Ru is larger and the number of surface active sites is smaller; Comparative Example 11 has not been treated with ultraviolet light, and the interaction between Ru and cerium dioxide is relatively weak.

[0054] The above-mentioned embodiments are preferred examples of the present invention and are not intended to limit the protection scope of the present invention.

Claims

1. A method for preparing a ruthenium / nano-cerium dioxide-based heterojunction catalyst, characterized in that: The following steps are involved: (1) precipitating cerium salt on a metal oxide substrate by a co-precipitation method, and subjecting the substrate to aging and calcination to obtain a nano-cerium dioxide heterojunction carrier; (2) The nano-cerium dioxide heterojunction carrier is mixed with a ruthenium source, and after ultraviolet light reduction treatment, the ruthenium / nano-cerium dioxide-based heterojunction catalyst is obtained.

2. The preparation method according to claim 1, characterized in that: In step (1), the ruthenium source is ruthenium chloride or carbonyl ruthenium, and the content of ruthenium element in the ruthenium source is 0.5wt%-3wt% of the nano-cerium dioxide heterojunction carrier.

3. The preparation method according to claim 2, characterized in that: In step (1), ammonia water, sodium carbonate or potassium hydroxide is used as a precipitant to precipitate the cerium salt on the metal oxide substrate.

4. The preparation method according to claim 3, characterized in that: In step (1), the metal oxide substrate is one of aluminum oxide, titanium oxide, magnesium oxide, vanadium oxide or molybdenum oxide.

5. The preparation method according to claim 4, characterized in that: In step (1), the cerium salt is one of cerium nitrate, ammonium cerium nitrate, cerium chloride or cerium sulfate.

6. The preparation method according to claim 5, characterized in that: In step (1), in the nano-cerium dioxide heterojunction carrier, the particle size of the nano-cerium dioxide is 5-20 nm.

7. The preparation method according to claim 6, characterized in that: In step (1), the precipitation pH is 8-12, the aging time is 4-24 hours, and the calcination temperature is 500-800°C.

8. The preparation method according to claim 7, characterized in that: The step (2) specifically comprises: mixing the nano-cerium dioxide heterojunction carrier with a ruthenium source, irradiating the mixture with a 200-400W UV lamp for 0.5-4 hours, centrifuging, washing and drying at 100-120°C to obtain the ruthenium / nano-cerium dioxide-based heterojunction catalyst.

9. A ruthenium / nano-cerium dioxide-based heterojunction catalyst, characterized in that: The ruthenium / nano-cerium dioxide-based heterojunction catalyst is prepared by the preparation method described in any one of claims 1 to 8.

10. An application of a ruthenium / nano-cerium dioxide-based heterojunction catalyst, characterized in that: When the reaction temperature is 400-700°C, the reaction pressure is 0-1MPa, and the space velocity is 1000-50000h -1 Under the conditions of, the ruthenium / nano-cerium dioxide-based heterojunction catalyst prepared by the preparation method according to any one of claims 1 to 8 or the ruthenium / nano-cerium dioxide-based heterojunction catalyst according to claim 9 is used to catalyze the decomposition of ammonia to produce hydrogen.

Citation Information

Patent Citations

  • Preparation method of CO selective methanation catalyst

    CN101607200A

  • Nano-plate with precious metal and method for preparing nano-plate

    CN105664929A

  • Application of metal-loaded catalyst taking rare earth carbonate as carrier precursor in ammonia decomposition reaction

    CN111215063A